2015
DOI: 10.3171/2014.9.jns14346
|View full text |Cite
|
Sign up to set email alerts
|

Sensory abnormalities and masticatory function after microvascular decompression or balloon compression for trigeminal neuralgia compared with carbamazepine and healthy controls

Abstract: There is a lack of comparative papers regarding the outcomes of neurosurgery in patients with iTN. The objective of this study was to investigate sensory thresholds and masticatory function in 78 patients with iTN who underwent microvascular decompression (MVD) or balloon compression (BC), and compare these treatments with carbamazepine and 30 untreated healthy controls. methods The authors conducted a case-controlled longitudinal study. Patients were referred to 1 of 3 groups: MVD, BC, or carbamazepine. All p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 29 publications
0
16
1
1
Order By: Relevance
“…Interestingly, there was a postinterventional drop tendency of mean MDT z scores from -4.27 to -7.58 at follow-up (p ¼ 0.15) that was also identified in another case-control longitudinal study after trigeminal ganglion balloon compression, but not following MVD. 30,36 The same study refers to increased cold and warm thresholds after MVD and balloon compression that is not supported by our data concerning RFT.…”
Section: Discussion Postinterventional Clinical Improvement and Procecontrasting
confidence: 54%
“…Interestingly, there was a postinterventional drop tendency of mean MDT z scores from -4.27 to -7.58 at follow-up (p ¼ 0.15) that was also identified in another case-control longitudinal study after trigeminal ganglion balloon compression, but not following MVD. 30,36 The same study refers to increased cold and warm thresholds after MVD and balloon compression that is not supported by our data concerning RFT.…”
Section: Discussion Postinterventional Clinical Improvement and Procecontrasting
confidence: 54%
“…A study of patients with TN before and after decompression surgery found that although pain and masticatory function improved after surgery, QST identified the development of subtle new sensory deficits following surgery. 134 QST could also serve as a predictive biomarker, forecasting potential efficacy to various treatment options.…”
Section: Psychophysical Biomarkersmentioning
confidence: 99%
“…There are cases when pain returns without apparent reasons [10][11][12][13][14][15][16][17] . Pain episodes cause extreme jaw restriction, including daily functions such as swallowing, speaking and teeth-brushing; sensory abnormalities are also frequent in these patients 18 . The IHS 7 has included two other conditions with similar clinical expression: painful trigeminal neuralgia due to multiple sclerosis (differentiated by disease diagnosis and for not being mandatorily bilateral) and painful trigeminal neuropathy attributed to injury (caused by invasive process in the region of the trigeminal nerve).…”
Section: Trigeminal Neuralgiamentioning
confidence: 99%
“…Among them, microvascular decompression has excellent long term results, although with increased surgery-inherent risks. There are less adverse effects on the masticatory system as compared to trigeminal ganglion balloon compression 18 which is a surgical percutaneous modality that can be used to treat TN 20 . Anesthetic block during balloon compression may decrease intraoperative complications 30 .…”
Section: Trigeminal Neuralgiamentioning
confidence: 99%